(untitled) (Research, Society and Development, 2020)
Scientific Dissemination magazines have an important role today as a resource capable to share the scientific knowledge. This tool, when combined with health issues such as epidemiology, allows to bring the reader closer to issues of great importance to a society in general, such as sexually transmitted infections, arboviruses, vaccines and other health conditions. This study has as its research objective to investigate how Epidemiology is approached in Scientific Dissemination magazines. For this, the magazine of Scientific Dissemination Superinteressante was selected and analyzed according to the aspects of the language and the thematic. It was observed that the language was presented in a clear and easy way to understand for the reading public. In relation to the thematic, health contents can be useful, in order to bring the public closer to scientific knowledge and assist in the promotion of health and its values. However, it draws attention to the fact that this texts deserve a betterment in relation to the epidemiological profile of diseases and their causes in the brazilian scenario.